2018
DOI: 10.1007/s10151-018-1821-2
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral versus unilateral botulinum toxin injections for chronic anal fissure: a randomised trial

Abstract: BackgroundBotulinum toxin injected into the internal anal sphincter is used in the treatment of chronic anal fissure but there is no standardised technique for its administration. This randomised single centre trial compares bilateral (either side of fissure) to unilateral injection.MethodsParticipants were randomised to receive bilateral (50 + 50 units) or unilateral (100 units) Dysport® injections into the internal anal sphincter in an outpatient setting. Injection-related pain assessed by visual analogue sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
(30 reference statements)
1
14
0
Order By: Relevance
“…They performed 50 IU unilaterally in the rst group and 50 IU bilaterally in the second group. According to the results of this study, they reported that unilateral 50 IU BT was su cient to prevent recurrence and e cacy [20].…”
Section: Discussionmentioning
confidence: 79%
“…They performed 50 IU unilaterally in the rst group and 50 IU bilaterally in the second group. According to the results of this study, they reported that unilateral 50 IU BT was su cient to prevent recurrence and e cacy [20].…”
Section: Discussionmentioning
confidence: 79%
“…An earlier study observed that dietary bran supplements and warm sitz baths effectively treat acute anal fissures [ 22 ]. The other medical management process is termed as “chemical sphincterotomy”, where pharmacological agents such as glyceryl trinitrate or calcium blockers, and botulinum toxin (BT) injection are applied to treat chronic anal fissures [ [8] , [9] , [10] , [11] ]. However, it is not considered an effective treatment strategy and has a low success rate [ 6 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, The American Society of Colon and Rectal Surgeons (ASCRS) guidelines recommend that for the initial nonsurgical management of anal fissure, the patient should be recommended stool softeners, high fiber diet, and warm sitz bath [ 7 ]. Application of pharmacological agents such as glyceryl trinitrate or calcium blockers, and botulinum toxin (BT) injection are other treatment strategies, which are also termed as “chemical sphincterotomy” [ [8] , [9] , [10] , [11] ]. However, the success rate (65–75%) of this treatment strategy is significantly lower than as observed in surgical sphincterotomy [ [11] , [12] , [13] ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the use of a single posterior injection is more tolerable and less painful than bilateral injection [317]. Few other studies analyzed the role of Botulinum toxin for the treatment of chronic AF [318,319]. The results of these studies regarding the dose, preparation, and the site of injection are interesting but cannot be extended to the treatment of acute anal fissures.…”
Section: Pain Control (See Question 7d)mentioning
confidence: 99%